The accuracy of different FRAX tools in predicting fracture risk in Japan: A comparison study. (24th April 2020) - Xu, Gang; Yamamoto, Norio; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Igarashi, Kentaro; Taniguchi, Yuta; Araki, Yoshihiro; Yonezawa, Hirotaka; Morinaga, Sei; Tsuchiya, Hiroyuki
Introduction: The web version of Fracture Risk Assessment (FRAX) tool is widely used in many countries to predict the 10-year probability of major osteoporotic fracture (MF) and hip fracture (HF) rate. However, other FRAX tools, calculator older version (first generation), calculator new version (second generation), and application of mobile software had also been used in Japan. Purpose: The aim of this study is to investigate the consistency of results obtained from the four predicting tools for MF and HF rate in both male and female groups. Methods: The data were extracted from 2016 medical examination report of Japanese Ministry of Health of Labor and Welfare. The MF and HF rates were calculated from 40 to 90 years old under different risk factors using four FRAX tools while the consistency of predicting value was evaluated. Results: The predicted MF or HF rates were extremely similar among calculator new version, mobile software, and website version in each risk factors. On other hand, for calculator older version, the predicted MF or HF rates are a little higher than other versions. The significant difference is only present in patients aged 75 and above, and this exceeds the FRAX threshold older than 75 years old by Japanese Society for Bone and Mineral Research. Conclusions: The application of four FRAX tools generated consistent results in predicting the 10-year probability of major osteoporotic fracture and HF for clinical practice, which provides an effective evidence for clinical application.